Entanglement of Formation for a Family of 2 - D)-Dimensional Systems - Retamal-Abarzua, J; Lopez-Cabrera, C (2012)
Entanglement of formation for arbitrary mixed states in a (2 - 2)-dimensional Hilbert space is well known. For higher-dimensional mixed states analytical expressions for quantifying entanglement exist for a particular family of states. In this work, we calculate analytically the entanglement of formation for a family of bipartite (2 - d)-dimensional mixed states which can be obtained from tripartite 2 - 2 - d pure states following the entanglement relations obtained by Koashi and Winter. © 2012 American Physical Society.